Risk Management theory: the integrated perspective and its application in the public sector - Cienfuegos Spikin, Ignacio (Estado, Gobierno y Gestión Pública, 2013)
This article aims to discuss in a normative way, the foundations of the theory of risk management, showing its evolution and reviewing the main best practices. As consequence, after a quick description of the current environment into which public and private organizations currently struggle, we proceed to develop a clear definition of risk. We introduce then, the fundamental aspects of risk management and the practices prescribe in the literature. Moreover, we describe the fundamental elements that have marked the transition from the "silo" approach or compartmental perspective of risk management, to the integrated risk management approach. At the end of the article, we discuss the application of risk management in the public sector, describing its difference from private risk management.